TRANSPARENCY IN GOVERNMENT PROCUREMENT ACCOUNTING AND ITS IMPACT ON ANTI-CORRUPTION EFFORTS - Shella Gilby Sapulette; Alend Talla; Franco Benony Limba (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study examines the role of transparency in government procurement accounting and its implications for strengthening anti-corruption efforts. Using a literature review approach, the research explores various scholarly works, reports, and empirical studies that highlight how transparent procurement practices serve as a fundamental mechanism in minimizing opportunities for corruption, enhancing accountability, and promoting trust in public institutions. The findings indicate that the implementation of transparency in procurement accounting is not only limited to the disclosure of financial information but also involves the standardization of procedures, the establishment of monitoring systems, and the integration of digital platforms that allow greater access to procurement data. Furthermore, transparency has been shown to foster competition among suppliers, reduce collusion, and improve the efficiency of resource allocation in the public sector. However, challenges remain in the form of bureaucratic resistance, regulatory inconsistencies, and limited capacity in monitoring mechanisms. This study concludes that transparency in government procurement accounting is a critical pillar in anti-corruption strategies, and its success depends on comprehensive institutional commitment, public participation, and continuous reform in governance practices.